Financial Prospect to The Application of High Rate Water Treatment Plant System - Mohajit Mohajit (Teknik Lingkungan Universitas Islam Indonesia, 2010)
The High Rate Water Treatment Plant (HR-WTP) system, which is inexpensive, effective and efficient, has been developed to reduce the common operational problems, and also as an alternative for the development of water treatment plant systems capacity in Indonesia.Implementation of HR-WTP system in up-rating of the Dekeng-WTP system at PDAM Kota Bogor proved successful in increasing the plant capacity from its original of 500 Lps to more than 1200 Lps. The performance of the WTP system was also significantly improved from poor performance to very good performance.The investment cost for up-rating proved competitive when compared to alternatively constructing a new WTP system with an equivalent capacity and performance. Application of HR-WTP systems for the development of WTP system in Indonesia, i.e. rehabilitation, up-grading, and up-rating, as well as construction of a new WTP system, is expected to bring technical, financial, and economic benefits. This new approach might be an innovative solution to the challenge of Millennium Development Goals in Water Supply Sector in Indonesia, where an additional capacity of ca 150,000 Lps should be developed within a 15 years period with an estimated budget of US 1.5 billions. This budget might be reduced to less than 50% through the application of the HR-WTP system.